Simulation and optimization of a continuous biodiesel plant using nonlinear programming - Alvarães, Adan de Oliveira; Prata, Diego Martinez; Santos, Lizandro de Sousa (Energy (Oxford), 2019)
The continuous production of biodiesel is achieved through a sequence of stages such as reaction, absorption, decantation, and product distillation. These steps require certain performance criteria that must be optimized. Several works have addressed the optimization of the design of biodiesel plants, and these have usually examined modifications to the dimensions and types of equipment or energy integration. However, there is only limited literature available on determining optimal operating conditions for existing processes. In this paper, the steady-state optimization of a soybean continuous biodiesel plant is proposed. To this end, a mathematical model to describe the chemical kinetics of soybean oil transesterification was developed and incorporated into a chemical process simulator. The optimization procedure is based on multidimensional Sequential Quadratic Programming (SQP), in which the primary objectives were to minimize the plant’s energy consumption subject to a minimum of 99 wt% biodiesel purity. The results reveal that the optimization of the current process allows a 4.45% reduction in energy consumption compared to the base case. Besides, the study also evidenced that the optimization approach can be applied to recalculate the optimal point when possible disturbances can deviate the system from a steady state. •SQP is used to optimize a continuous biodiesel process.•Compared to base-case simulation, the framework can reduce energy consumption.•The energy consumption could be reduced 4.45%.•The energy consumption could be reduced for different operating points.